Perancangan Basis Data Improvement Dashboard Application: Studi Kasus pada Padang Karunia Group - Ayuliana Ayuliana; Nailur Rahma; Titis Aulia; Ratri Permatasari (Bina Nusantara University, 2013)
Padang Karunia Group received a lot of inputs from its employees for improvement collected manually by an administrator. The more input from employees, the more difficult to be collected manually. Therefore Padang Karunia Group took the initiative to create an intranet application to save the inputs in a database. Based on this problem, a research is done to develop database applications in the form of dashboard to collect criticisms and suggestions of employees over the web. This application is expected to assist and facilitate the management of the company, especially in the gathering criticism and suggestions from employees who are then evaluated for company improvement. We uses the database design method based on database application lifecycle, including requirements collection and analysis, conceptual database design, logical database design, DBMS selection, physical database design, and implementation. The results achieved are a database design anda web-based dashboard application that collects criticisms and suggestions. The advantage of using this application is that the company can easily accept criticism and suggestions from employees, simplify storage and data management criticism and suggestions, create reports, and reduce the cost of data collection and the process that was previously done manually. Through the database created, the data management of criticisms and suggestions of employees can be done better.